2018
DOI: 10.1038/s41598-018-36251-0
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 is associated with cancer stem-like properties in colorectal cancer

Abstract: Sox2 is known as the undifferentiated cell marker. Recent studies have shown that Sox2 may also be involved in the maintenance of cancer stem cells (CSCs) in skin and bladder cancers. In this study, we aimed to clarify the role of Sox2 in colorectal CSCs. Sox2 expression was measured in colon cancer cells and colorectal clinical samples by qRT-PCR and western blot analysis. To visualize the active Sox2 mRNA production, we generated a Sox2 promoter-dependent DsRed fluorescence emission system. Colon cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 34 publications
4
72
0
2
Order By: Relevance
“…The expression of a downstream target gene of ZEB1, MMP14 (a matrix metalloprotease), was also consistently suppressed in MeCP2-depleted HCT116 cells ( Figure 5C). Moreover, the expression of cancer stem cell surface antigens, including CD133 (Prominin-Like Protein 1) [21], KLF4 (Kruppel-like factor 4) [22], and Sox2 (SRY-Related HMG-Box Gene 2) [23], was reduced after MeCP2 inhibition ( Figure 5C), consistent with the aforementioned observations in the sphere formation assay. Expression of full-length MeCP2 restored ZEB1 mRNA expression in MeCP2-depleted cells ( Figure 5D left), but truncated or mutated versions of MeCP2 (Table S5, the sequence of wild type or depletion MeCP2 CDS) had no effect ( Figure 5D right).…”
Section: Zeb1 Is the Major Effector Of Mecp2supporting
confidence: 84%
“…The expression of a downstream target gene of ZEB1, MMP14 (a matrix metalloprotease), was also consistently suppressed in MeCP2-depleted HCT116 cells ( Figure 5C). Moreover, the expression of cancer stem cell surface antigens, including CD133 (Prominin-Like Protein 1) [21], KLF4 (Kruppel-like factor 4) [22], and Sox2 (SRY-Related HMG-Box Gene 2) [23], was reduced after MeCP2 inhibition ( Figure 5C), consistent with the aforementioned observations in the sphere formation assay. Expression of full-length MeCP2 restored ZEB1 mRNA expression in MeCP2-depleted cells ( Figure 5D left), but truncated or mutated versions of MeCP2 (Table S5, the sequence of wild type or depletion MeCP2 CDS) had no effect ( Figure 5D right).…”
Section: Zeb1 Is the Major Effector Of Mecp2supporting
confidence: 84%
“…Moreover, a causative role of B4GALNT2 in the control of these genes was supported by the observation that in the TCGA cohorts of high and low B4GALNT2 expressers, the mean level of expression of these genes was in some cases significantly consistent with that observed in LS174T cells. Among the genes showing significant inverse association with B4GALNT2 expression in TCGA, SOX2 is particularly relevant for its role in CRC stemness [27]. Its dramatic down-regulation in S2/S11 clones can certainly contribute to explaining their reduced ability to grow in non-adherent conditions and their reduced content of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly studied are SOX2, OCT4, and Nestin. SOX2 is a transcription factor expressed in nervous system at the earliest developmental stages and is widely used as a marker for undifferentiated normal and CSCs of various origin including neuronal (Takeda et al, ). Tanaka et al () found that SOX B1 and SOX C transcription factor groups interact with POU family transcription factors and activate the Nestin neural enhancer in mouse and chicken embryos.…”
Section: Discussionmentioning
confidence: 99%